LabVIEW FPGA Based BLDC Motor Control by Using Field Oriented Control Algorithm - (:unkn) unknown (IEEE, 2020)
BLDC (Brushless Direct Current) motors are widely used today due to its high reliability and high efficiency. These motors are synchronous motors that have a linear relationship between voltage-speed and current-torque. To control these kinds of motors, inverters are needed. Inverters create a rotational movement in the motor by switching at the appropriate time according to the rotor position information. Rotor position is obtained in two ways, with and without sensor. Sensor method uses encoders, resolvers or hall effect sensor. Hall-effect sensors are generally preferred for the control of BLDC motors in terms of cost. In this study, the rotor position was obtained by using hall-effect sensor. Pulse Width Modulation (PWM) is used to control the frequency and voltage of the inverters. Today, Sinusoidal PWM (SPWM) and Space Vector Pulse Width Modulation (SVPWM) techniques are frequently used in such applications. This study explains the development of a Field Oriented Control Algorithm (FOC) based on SVPWM technique by using the LabVIEW FPGA Module for a BLDC Motor. It also shows the effects of using PI and FFC (Feed Forward Control) algorithm together and separately in the controller for the control of I-d and I-q reference currents. In addition, simulation of all project was developed and run in Matlab/Simulink.
Keywords: BLDC; LabVIEW-FPGA; PI regulators; FFC; FOC; hall effect sensors; SVPWM